2016
DOI: 10.1016/j.tcb.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

AMPK: An Energy-Sensing Pathway with Multiple Inputs and Outputs

Abstract: Summary The AMP-activated protein kinase (AMPK) is a key regulator of energy balance expressed ubiquitously in eukaryotic cells. Here, we review the canonical adenine nucleotide-dependent mechanism that activates AMPK when cellular energy status is compromised, as well as other, non-canonical activation mechanisms. Once activated, AMPK acts to restore energy homeostasis by promoting catabolic pathways, resulting in ATP generation, and inhibiting anabolic pathways that consume ATP. We also review the various hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
594
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 716 publications
(625 citation statements)
references
References 75 publications
(105 reference statements)
7
594
1
1
Order By: Relevance
“…Because AMPK is immediately downstream of, and activated by, the tumor suppressor LKB1, because it inhibits cell growth and proliferation and switches off the growth-promoting target-of-rapamycin complex-1 (TORC1) when activated (5,40), and because use of the AMPK-activating drug metformin is associated with a lower risk of cancer in diabetics (41), it had been widely assumed that AMPK was a tumor suppressor. Although AMPK may indeed initially suppress the development of rapidly growing tumors and there may therefore be selection pressure for the LKB1-AMPK pathway to be downregulated (42), complete loss of function of AMPK in human cancers appears to be rare.…”
Section: Discussionmentioning
confidence: 99%
“…Because AMPK is immediately downstream of, and activated by, the tumor suppressor LKB1, because it inhibits cell growth and proliferation and switches off the growth-promoting target-of-rapamycin complex-1 (TORC1) when activated (5,40), and because use of the AMPK-activating drug metformin is associated with a lower risk of cancer in diabetics (41), it had been widely assumed that AMPK was a tumor suppressor. Although AMPK may indeed initially suppress the development of rapidly growing tumors and there may therefore be selection pressure for the LKB1-AMPK pathway to be downregulated (42), complete loss of function of AMPK in human cancers appears to be rare.…”
Section: Discussionmentioning
confidence: 99%
“…We previously confirmed that PMFs, particularly 5,7-dimethoxyflavone in KPE, improved metabolism in muscle cells by activating AMPK [24]. AMPK is known to play a critical role in the regulation of energy homeostasis and is related to physical fitness, endurance, and fatigue [41][42][43][44][45][46][47][48]. For example, 5-aminoimidazole-4-carboxyamide ribonucleotide (AICAR), an AMPK agonist, was reported to increase running endurance by 44% and decrease body fat in mice following its oral administration for 4 weeks [48].…”
Section: Discussionmentioning
confidence: 72%
“…In yeast, scarcity of nutrients and energy results in the activation of SNF1 [73]. When activated, AMPK restores energy balance by switching off ATP-consuming anabolic pathways and switching on ATP generating catabolic pathways such as fatty acid oxidation [74]. Further, we identified 10 putative CDPKs in the S. neurona, including CDPK1 (SRCN_3314), CDPK2 (SRCN_4390), CDPK2A (SRCN_2165), CDPK3 (SRCN_3701), CDPK4 (SRCN_6606), CDPK5 (SRCN_3583), CDPK6 (SRCN_3011), CDPK7 (SRCN_6597), CDPK8 (SRCN_5948) and CDPK9 (SRCN_5812).…”
Section: Discussionmentioning
confidence: 99%